Information from the Peace Movement of the German Democratic Republic = Informations du Mouvement de la Paix de la République Démocratique Allemande. - Peace Council of the German Democratic Republic (Berlin : Peace Council of the German Democratic Republic, 1962)
Bibliotheek Camille Huysmans
Periodiciteit: maandelijks
Engels
Periodiek
Keywords: pacifistische pers; Oost-Duitsland.